Political Microtargeting and Online Privacy: A Theoretical Approach to Understanding Users’ Privacy Behaviors - Johanna Schäwel; Regine Frener; Sabine Trepte (Media and Communication, 2021)
Social media allow political parties to conduct political behavioral targeting in order to address and persuade specific groups of users and potential voters. This has been criticized: Most social media users do not know about these microtargeting strategies, and the majority of people who are aware of targeted political advertising say that it is not acceptable. This intrusion on personal privacy is viewed as problematic by users and activists alike. The overarching goal of this article is to elaborate on social media users’ privacy perceptions and potential regulating behaviors in the face of political microtargeting. This work is theoretical in nature. We first review theoretical and empirical research in the field of political microtargeting and online privacy. We then analyze how privacy is experienced by social media users during political microtargeting. Building on our theoretical analysis, we finally suggest clear-cut propositions for how political microtargeting can be researched while considering users’ privacy needs on the one hand and relevant political outcomes on the other.